Knowledge Level of Adolescent Red Cross Students in First Aid for Syncope Handling - Pipin Yunus; Haslinda Damansyah; Nita M. Talib; Abdul Rahman Karim; Fahrianto Djarumia; Oktafian Mutoneng (Journal La Medihealtico, 2022)
Syncope is a temporary loss of consciousness consequence hypoperfusion cerebral global transient characterized with onset fast, duration which short and recovery spontaneous. Lost consciousness due to decreased blood flow to system Activation reticular and no need therapy electricity or chemistry for back to normal . The purpose of this study was to determine the level of knowledge of Adolescent Red Cross (PMR) students in first aid for handling syncope at SMA Negeri 1 Telaga Biru . This study uses a quantitative descriptive research method with a sample of 20 respondents obtained by using consecutive sampling technique. The results showed that 16 respondents lacked knowledge and 4 respondents had good knowledge. It can be concluded that this shows that the level of knowledge of Adolescent Red Cross (PMR) students in first aid for handling syncope is still in the poor category.